Two-period e-commerce platforms operation strategies considering the difference in product quality perception - Bo Xie; Qiqi Guo; Yingying Cheng; Muqing Niu (PLoS ONE, 2026)
The difference in consumer perceptions of product quality influences consumers’ propensity to purchase through various channels, thereby affecting the profit of e-commerce platforms and manufacturers. This factor is a critical consideration for e-commerce platforms when formulating their operational strategies in a multi-channel competitive environment. This study focuses on a product retail supply chain comprising two e -commerce platforms, two manufacturers, and strategic consumers. Innovatively, we construct a two-period dynamic pricing game model to compare commission-based and self-operated models for the platforms and deeply explore the impact of consumers’ product quality perception differences on pricing strategies and platform operation model choices. Four scenarios are considered: self-operated model under simultaneous decision-making, commission-based model under simultaneous decision-making, self-operated model under successive decision-making, and commission-based model under successive decision-making. Results show that as the probability of consumers perceiving high-quality products increases, both e-commerce platforms and manufacturers can enhance their profit by raising prices. Moreover, when platforms make decisions simultaneously, they should choose the commission-based model. In contrast, when platforms make decisions sequentially, the leader platform should choose the self-operated model, while the follower platform should choose the commission-based model. In particular, in the context of successive decision-making, after attracting consumers through the low-price strategy in the first period, the leader platform can still effectively maintain market share even if the price is raised in the second period.